The compact pulse electron accelerator; 3rd Euro-Asian Pulsed Power Conference and 18th International Conference on High Power Particle Beams 2010 (EAPPC/BEAMS 2010), Jeju, Korea, 10-14 October 2010 - Nashilevskiy A. V. Aleksandr Vladimirovich; Ezhov V. V. Vitali Vladimirovich; Kanaev G. G. Gennady Grigorevich; Remnev G. E. Gennady Efimovich (2010, 2010)
В фонде НТБ ТПУ отсутствует